Physiological Responses during Competitive Sports Aerobics Exercise - Roma Aleksandravičienė; Arvydas Stasiulis (Lithuanian Sports University, 2018)
The aim of this study was to characterize heart rate (HR), oxygen uptake and pulmonary ventilation during competitive aerobic gymnastics routine in a group of elite women athletes. The subjects were Lithuanian aerobic women gymnasts, members of national team (21.6, 4.4) years old). All subjects performed a maximal incremental treadmill test in the laboratory and competitive aerobic gymnastics exercises in group category. Heart rate was continuously recorded using the heart rate measurement equipment Polar ACCUREX-Plus. During the incremental treadmill test HR deflection point and other parameters of aerobic capacity were determined from the relationship of HR to running speed. During the aerobic gymnastics routine pulmonary gas exchange parameters and heart rate were continuously measured using the telemetric equipment Cortex 3B. The changes of HR, minute ventilation and oxygen uptake were analyzed by adopting monoexponential function. The results showed that HR values during the competitive aerobic gymnastics routine were higher than HR break point which is near the lactate accumulation threshold (reaching 95.2 (4.2)% of maximal HR). Oxygen uptake during competitive routine reached 81.3 (5.8)% of maximal oxygen uptake. Rather high blood lactate accumulation (7.50 mmol / l) at the third minute after exercise show the high intensity of exercise. These results allows us to consider that aerobic gymnastics is a sport with high cardiorespiratory and metabolic demands, in which aerobic and anaerobic sources are intensely activated. Keywords: aerobic gymnastics, aerobic capacity, pulmonary gas exchange, lactate, heart rate deflection point.